Geomorphological processes of a Mediterranean urbanized beach (Sardinia, Gulf of Cagliari). Issue 2 (13th November 2018) - De Muro, Sandro; Porta, Marco; Pusceddu, Nicola; Frongia, Paolo; Passarella, Marinella; Ruju, Andrea; Buosi, Carla; Ibba, Angelo
ABSTRACT: In this study, we present a comprehensive map of a microtidal wave-dominated beach system based on an interdisciplinary sea–land approach and with the purpose of supporting a sustainable and successful beach management. The study area is located in a highly urbanized/industrialized coastal sector of the W side of Cagliari Gulf (S Sardinia, W Mediterranean). In theMain Map (1:15, 000 scale), static and dynamic features of the beach system and adjacent inner shelf are divided into thematic sections, including geomorphological elements, bathymetry, sedimentological distribution, benthic habitat (mainly Posidonia oceanica meadow), hydrodynamics and anthropogenic features. The map constitutes an example of multidisciplinary benchmark to allow for long-term planning and management of this highly urbanized beach system. It is able to provide a substantial scientific support to policy-makers towards environmental restoration and sustainable development.